2021
DOI: 10.3390/molecules26185528
|View full text |Cite
|
Sign up to set email alerts
|

Valorization of Moroccan Bentonite Deposits: “Purification and Treatment of Margin by the Adsorption Process”

Abstract: The main objective of this work was to contribute to the reduction in the contamination of phenolic compounds contained in margin by an adsorption process on two types of raw bentonite. The margin used in the studies was collected from a semi-modern oil mill located in the Nador–Morocco region. The results of the physico-chemical analyses showed that the effluents of the oil mills showed that they are highly polluted, particularly in terms of the total suspended solids (TSS), chemical oxygen demand (COD), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…The band observed at 721 cm −1 and a sharp band at 623 cm −1 indicated Si-O stretching due to the presence of quartz [49,50]. The band observed at 522 cm −1 is corresponded to the deformation mode (bending vibration) of Si-O-Al group in octahedral, while the band at 465 cm −1 is assigned to the Si-O-Si deformation band (bending vibration) [51]. Based on these results, the Ca-MMT clay and 5% Ca-MMT/CPE have a strong adsorption property toward the VILD drug compared to graphite.…”
Section: Structural Characterization Of the Proposed Working Electrodementioning
confidence: 99%
“…The band observed at 721 cm −1 and a sharp band at 623 cm −1 indicated Si-O stretching due to the presence of quartz [49,50]. The band observed at 522 cm −1 is corresponded to the deformation mode (bending vibration) of Si-O-Al group in octahedral, while the band at 465 cm −1 is assigned to the Si-O-Si deformation band (bending vibration) [51]. Based on these results, the Ca-MMT clay and 5% Ca-MMT/CPE have a strong adsorption property toward the VILD drug compared to graphite.…”
Section: Structural Characterization Of the Proposed Working Electrodementioning
confidence: 99%
“…In this sense, Azizi et al [19] reported that during the summer period, the bivalves increase their body weight, therefore, the concentration of heavy metals will be diluted in flesh of the mussels. Considering the environmental parameters, the bioaccumulation of metals was higher in winter, probably due to the slower growth at cooler temperature [13,20,21].…”
Section: Temporal Variation Of Cu LI and Mn In Whole Tissues Of Musselsmentioning
confidence: 99%
“…In this sense, the accumulation of heavy metal in shellfish from the marine coasts must be monitored regularly to give information on the risk levels for consumer. Monitoring programs remain among the best tools to know and control metal pollutants in aquatic ecosystems [5][6][7][8]. The mussels, sessile species, have been widely investigated and used to monitor metal pollution in aquatic environments and to reveal the bioavailability of metals by marine biota [9,10].…”
Section: Introductionmentioning
confidence: 99%